Leading Causes of In-Hospital Death of Older Patients of Different Age Groups in Shanghai - Gong Y; Liu Q; Hu Q (Dove Medical Press, 2024)
Yu Gong,1,* Qianxia Liu,2,* Qiang Hu3 1Department of Internal Medicine, Division of Nephrology, Telemedicine Center, Shanghai Municipal Eighth People's Hospital, Shanghai, People's Republic of China; 2Department of Medical Affairs Management, Division of Medical Record Management, Shanghai Municipal Eighth People's Hospital, Shanghai, People's Republic of China; 3Department of Surgery, Shanghai Municipal Eighth People's Hospital, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Yu Gong, Department of Internal medicine, Division of Nephrology, Telemedicine Center, Shanghai Municipal Eighth People's Hospital, 8 Caobao Road, Shanghai, 200235, People's Republic of China, Email gyfd66@sina.com Qiang Hu, Department of Surgery, Shanghai Municipal Eighth People's Hospital, 8 Caobao Road, Shanghai, 200235, People's Republic of China, Email huqiang20230828@163.comBackground: Despite great achievements in clinical medicine, the in-hospital mortality of older patients remains high. How to reduce the in-hospital mortality of older inpatients is of great clinical value in clinical practice. This study is to analyze the leading causes of in-hospital death of older inpatients of different ages in Shanghai.Methods: An observational study was conducted in Shanghai. A total of 3894 older inpatients (≥ 60 years old) were investigated. According to the age stratification standard of World Health Organization, they were divided into young older patients group (aged 60 to 74), old older patients group (aged 75 to 89) and very old patients group (aged ≥ 90). Diseases of in-hospital death of older inpatients in different age groups were classified according to the 10th edition of the International Classification of Diseases. Constituent ratio of causes of in-hospital death in each group was analyzed.Results: The constituent ratio of pulmonary infection had the highest rate of in-hospital death in older patients. The constituent ratio of lung malignant tumors had the highest rate of in-hospital death in young older patients. The constituent ratio of pulmonary infection had the highest rate of in-hospital death in old older patients. The constituent ratio of pulmonary infection had the highest rate of in-hospital death in very old patients.Conclusion: The leading cause of in-hospital death of young older patients group was lung malignant tumor. The leading cause of in-hospital death of old older patients group and very older patients group was pulmonary infection. Great importance should be attached to the prevention of lung tumor and lung infection in the elderly. Results of this study will provide a basis for health administrative departments to formulate corresponding health-care policies for older patients.Keywords: causes of in-hospital death, older patients, age stratified analysis, lung malignant tumor, pulmonary infection